2022
DOI: 10.3390/md20010063
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of New Ceramides Isolated from the Red Sea Red Algae Hypnea musciformis in a Model of Ehrlich Ascites Carcinoma: LC-HRMS Analysis Profile and Molecular Modeling

Abstract: Different classes of phytochemicals were previously isolated from the Red Sea algae Hypnea musciformis as sterols, ketosteroids, fatty acids, and terpenoids. Herein, we report the isolation of three fatty acids—docosanoic acid 4, hexadecenoic acid 5, and alpha hydroxy octadecanoic acid 6—as well as three ceramides—A (1), B (2), and C (3)—with 9-methyl-sphinga-4,8-dienes and phytosphingosine bases. Additionally, different phytochemicals were determined using the liquid chromatography coupled with electrospray i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
(92 reference statements)
1
12
1
Order By: Relevance
“…So, many scientific papers were oriented to illustrate how these plants undergo their pharmacological effects. Previous studies involved green medicine as a crude extract of the whole plant [ 3 , 4 ], an extract of certain parts [ 5 , 6 ], purified natural compounds [ 7 , 8 , 9 ], or isolated certain bioactive fractions such as polyphenols, essential oils, saponins, alkaloids, polysaccharides, etc. [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, many scientific papers were oriented to illustrate how these plants undergo their pharmacological effects. Previous studies involved green medicine as a crude extract of the whole plant [ 3 , 4 ], an extract of certain parts [ 5 , 6 ], purified natural compounds [ 7 , 8 , 9 ], or isolated certain bioactive fractions such as polyphenols, essential oils, saponins, alkaloids, polysaccharides, etc. [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…354 Other structures were put forward although these were inconsistent with the spectroscopic data provided and are not shown here. 355…”
Section: Red Algaementioning
confidence: 99%
“…So, many scientific papers were oriented to illustrate how these plants undergo their pharmacological effects. Previous studies involved the green medicine as a crude extract of whole plant , Eltamany et al, 2022, an extract of certain parts (Goda et al, 2022, Duan et al, 2020, purified natural compounds , Habib et al, 2022 or isolated certain bioactive fractions such as polyphenols, essential oils, saponins, alkaloids & polysaccharides (Micale et al, 2020, Selim et al, 2022. Previous study reported the ability of C. scolymus L. to reduce fasting blood glucose level, A1C-derived average glucose (ADAG), and homeostatic model assessment (HOMA), that assess β-cell function and insulin resistance, in prediabetic patients (Rondanelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%